2016
DOI: 10.14739/2310-1237.2016.2.81128
|View full text |Cite
|
Sign up to set email alerts
|

Serrated polyps as precursor lesions of colorectal cancer: current status and future directions. Mini-review.

Abstract: Early diagnosis of colorectal cancer (CRC) is a very urgent problem, since this disease has second place among women and the third one among men in the structure of cancer pathology. According to recent data, CRC should be considered as a heterogeneous multifactorial family of diseases with different variants.Serrated polyps of the colon are obligate precancerous condition, which can transform into cancer due to genetic aberrations. Serrated polyps are a heterogeneous group of formations with different ways of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Serrated polyps are distinguished by typical serrated (jagged, sawtooth) appearance of crypts and their epithelial cover. Previously, only hyperplastic polyps were known as serrated polyps; moreover, it was believed that they didn't have malignant potential [6,7]. During the last 10 years it was revealed that serrated polyps are heterogenous group of neoplasms which can be precursors for CRC.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Serrated polyps are distinguished by typical serrated (jagged, sawtooth) appearance of crypts and their epithelial cover. Previously, only hyperplastic polyps were known as serrated polyps; moreover, it was believed that they didn't have malignant potential [6,7]. During the last 10 years it was revealed that serrated polyps are heterogenous group of neoplasms which can be precursors for CRC.…”
Section: ____________________________________________________________mentioning
confidence: 99%